Strategi Dakwah Digital Komunitas Pendakwah Keren Samarinda - Lulu Khumairo; Nurul Syobah; Fuad Fansuri; A. Rivai Beta (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2023)
The focus of this research is to explain the digital da’wah strategy of the Samarinda Keren (Cool) Da’wah Community by examining the da’wah process on social media through the personal accounts of the preachers. The results showed da’wah strategy of the Samarinda Cool Da’wah Community into three: (1) Manhaj al-’Athifi, (2) Manhaj al-Aqli, and (3) Manhaj-al-Hissi. In addition, the Introduction of mad’u or the third object of da’wah is by looking at the effect of the material presented, one of which is by looking at the response of mad’u through the comment column on whether to accept or reject. Preparing da’wah materials by the Qur’an and Hadith to determine a law that gives birth to various variants of science, by the current context and da’wah is carried out with the humility that characterizes it. Samarinda Cool Da’wah Community, utilizing social media as alternative to reach mad’u widely now.